The Relationship between Emotional Intelligence, Job Satisfaction, and Organizational Commitment among First‐Line Nurse Managers in Qatar - Mutaz I. Othman (21186827) (2024)
Background Emotional responses and the ability to regulate emotions among nurses, especially first‐line nurse managers, can influence various workplace dynamics. However, there is a knowledge gap regarding emotional intelligence, job satisfaction, and organizational commitment among nurses in Qatar, particularly first‐line nurse managers. Objectives The primary aim of this study is to determine if there is a significant relationship between emotional intelligence, job satisfaction, and organizational commitment among first‐line nurse managers (FLNMs) in Qatar. Design. This is a descriptive cross‐sectional correlational study. Settings The research took place at Hamad Medical Corporation in Qatar. Participants A total of 203 first‐line nurse managers participated in the study. Methods Participants were recruited using a convenience sample method. Data were collected using the Genos Emotional Intelligence Inventory—Concise, the three‐component model Employee Commitment Survey, and the short‐form Minnesota Satisfaction Questionnaire (MSQ). Results The findings showed that participants had average levels of emotional intelligence, job satisfaction, and organizational commitment. Notably, a significant, moderately positive relationship was observed between emotional intelligence and organizational commitment, as well as between job satisfaction and organizational commitment. A weak positive relationship was identified between emotional intelligence and job satisfaction. Differences in emotional intelligence were observed based on variables such as gender, age, and unit specialty. Organizational commitment varied based on the current position and hospital type, while job satisfaction differed based on the current position and education level. Conclusions The findings suggest that enhancing the emotional intelligence of first‐line nurse managers can potentially improve organizational commitment, job satisfaction, and, subsequently, healthcare outcomes. There is a need for further research to delve deeper into these factors and devise strategies aiming to boost the emotional intelligence and job satisfaction of first‐line nurse managers. Implications for Nursing Management The study provides empirical data from Qatar’s healthcare system, shedding light on FLNMs’ emotional intelligence, job satisfaction, and organizational commitment. Other Information Published in: Journal of Nursing Management License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1155/2024/5114659